2020
DOI: 10.1002/adfm.202000794
|View full text |Cite
|
Sign up to set email alerts
|

A‐Site Cation Engineering of Metal Halide Perovskites: Version 3.0 of Efficient Tin‐Based Lead‐Free Perovskite Solar Cells

Abstract: Pb-based metal halide perovskites (MHPs) have emerged as efficient light absorbers in third-generation photovoltaic devices, and the latest certified power conversion efficiency (PCE) of Pb-based perovskite solar cells (PSCs) has reached 25.2%. Despite great progress, Pb-based MHPs are affected by toxicity, which hinders their market entry in a potential future large-scale commercialization effort. Therefore, the exploration of Pb-free MHPs has become one of the alternative solutions sought in the community. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 162 publications
(174 reference statements)
1
88
0
Order By: Relevance
“…To our surprise the reaction produced a novel structure type based on a 'hollow' B-site deficient perovskite, (TzH) 11 (H 3 PO 2 )Sn 6 I 23 (1). While the B-site deficient perovskite structure has been reported previously, 14,15 1 represents the first example of a layered variant of this family. On leaving the same reaction mixture for 2 months, a 3D 'hollow' perovskite (TzH) 3 Sn 2 I 7 (2) is the dominant product.…”
mentioning
confidence: 61%
“…To our surprise the reaction produced a novel structure type based on a 'hollow' B-site deficient perovskite, (TzH) 11 (H 3 PO 2 )Sn 6 I 23 (1). While the B-site deficient perovskite structure has been reported previously, 14,15 1 represents the first example of a layered variant of this family. On leaving the same reaction mixture for 2 months, a 3D 'hollow' perovskite (TzH) 3 Sn 2 I 7 (2) is the dominant product.…”
mentioning
confidence: 61%
“…Although CsSnBr 3 possesses a stable cubic perovskite phase at room temperature, it is a wide band gap semiconductor with the main light absorption range of 350-700 nm. [88] CsSnI 3 with band gap of~1.3 eV (theoretical PCE over 30 %) [53,54] shows the greater potential as light absorber, but the highest PCE of reported PSCs based on CsSnI 3 is only 5.03 % up to now, [15] which is far below the theoretical limit. The main obstacles can be considered from three aspects: phase instability, poor film quality, and inferior interfaces of CsSnI 3 film.…”
Section: Current Challengesmentioning
confidence: 88%
“…Although all-inorganic PbÀ Sn alloying perovskites have been studied as the active layer of PSCs, where replacing 25 % Pb with Sn could improve the photovoltaic performance of PSCs with much improve phase stability and illumination stability, [52] AISPs-based PSCs are still worthy of in-depth study owing to their merits discussed above. However, the highest PCE of all-inorganic CsSnI 3 -based PSCs so far is only 5.03 %, [15] which is much lower than their theoretical limit over 30 %. [53,54] Promisingly, recent work has shown that PSCs based on all-inorganic CsGe 0.5 Sn 0.5 I 3 perovskite have reached PCE of 7.11 % with extremely attractive stability.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations